A Empirical Analysis: The Society's Knowledge of Zakat Payment in Islamic Banking - Fahmiah Akilah (Institut Agama Islam Negeri Parepare, 2022)
The purpose of this study is to analyze the behavior of Muslim communities in paying zakat, primarily through Islamic institutions in Indonesia, in order to develop strategies for increasing the number of zakat recipients nationally in order to enhance the welfare of the larger community. – In the absence of government regulations regarding the obligation of Muslim communities to pay zakat, the behavior of zakat payers can be influenced in two ways: by enhancing the understanding of zakat and by bolstering the credibility of zakat management institutions, particularly Islamic banks. Providing complete information to the public regarding the existence of zakat management institutions and what they have done and will do is essential. Never before has research been conducted on how individuals pay zakat. This study examines the behavior of selecting a location to pay zakat as well as obedience to God and the government, awareness without coercion, and awareness without coercion